Intellectuals - Johnson, Paul, 1928- (New York : Harper & Row, 1990)
This volume presents a portrait of the minds that have shaped the modern world. In a series of case studies, Rousseau, Shelley, Marx, Ibsen, Tolstoy, Hemingway, Bertrand Russell, Brecht, Sarte, Edmund Wilson, Victor Gollancz, Lillan Hellman, Cyril Connolly, Norman Mailer, James Baldwin, Kenneth Tyan, Noam Chomsky, and others are revealed as intellectuals both brilliant and contradictory, magnetic and dangerous. The author examines the rise of the intellectual as a sort of secular seer and moral arbiter, a role once filled by the priest or soothsayer. These intellectuals, in the author's opinion, promote themselves as possessing the moral authority to transform society, a claim that the author disputes.
Jean-Jacques Rousseau : 'an interesting madman' -- Shelley, or the heartlessness of ideas -- Karl Marx : 'howling gigantic curses' -- Henrik Ibsen : 'on the contrary!' -- Tolstoy : God's elder brother -- The deep waters of Ernest Hemingway -- Bertolt Brecht : heart of ice -- Bertrand Russell : a case of logical fiddlesticks -- Jean-Paul Sartre : 'a little ball of fur and ink' -- Edmund Wilson : a brand from the burning -- The troubled conscience of Victor Gollancz -- Lies, damned lies and Lillian Hellman -- The flight of reason.
Includes index.
Includes bibliographical references (pages 343-365).
Keywords: Intellectuals; Intellectual life; Civilization, Modern; Intellektueller; Social sciences